Measurement of hardness and friction properties of pencil leads for quantification of pencil hardness test. (16th November 2016) - Kim, Y.; Sung, A.; Seo, Y.; Hwang, S.; Kim, H.
Abstract : We have investigated the various properties of different types of pencil leads in order to quantify a pencil hardness test for reliability. The chemical composition and mechanical properties for different types of pencils (F, 2H, 4H, 6H and 8H) were measured using X-ray diffraction, nano-indentation and a tribometer. The values for nano-indentation hardness of the pencil leads are in the range of 0.3–0.8 GPa. A higher hardness grade in the pencil lead leads to a wider error range. The clay content of the lead seems to be proportional to the hardness of the pencil lead. Different crystalline phases in clays for each grade of pencil lead result in variations in the degree and distribution of the hardness. Consequently, the content of the crystalline phases in the clay affects deviations in the hardness.